MuSK Myasthenia Gravis—Potential Pathomechanisms and Treatment Directed against Specific Targets - Edyta Dziadkowiak; Dagmara Baczyńska; Marta Waliszewska-Prosół (Cells, 2024)
Myasthenia gravis (MG) is an autoimmune disease in which autoantibodies target structures within the neuromuscular junction, affecting neuromuscular transmission. Muscle-specific tyrosine kinase receptor-associated MG (MuSK-MG) is a rare, often more severe, subtype of the disease with different pathogenesis and specific clinical features. It is characterized by a more severe clinical course, more frequent complications, and often inadequate response to treatment. Here, we review the current state of knowledge about potential pathomechanisms of the MuSK-MG and their therapeutic implications as well as ongoing research in this field, with reference to key points of immune-mediated processes involved in the background of myasthenia gravis.